Analytical sensitivity and specificity of a loop-mediated isothermal amplification (LAMP) kit prototype for detection of Trypanosoma cruzi DNA in human blood samples. - Susana A Besuschio; Mónica Llano Murcia; Alejandro F Benatar; Severine Monnerat; Israel Cruz; Albert Picado; María de Los Ángeles Curto; Yutaka Kubota; Diana P Wehrendt; Paula Pavia; Yasuyoshi Mori; Concepción Puerta; et al. (Public Library of Science (PLoS), 2017)
This study aimed to assess analytical parameters of a prototype LAMP kit that was designed for detection of Trypanosoma cruzi DNA in human blood. The prototype is based on the amplification of the highly repetitive satellite sequence of T.cruzi in microtubes containing dried reagents on the inside of the caps. The reaction is carried out at 65°C during 40 minutes. Calcein allows direct detection of amplified products with the naked eye. Inclusivity and selectivity were tested in purified DNA from Trypanosoma cruzi stocks belonging to the six discrete typing units (DTUs), in DNA from other protozoan parasites and in human DNA. Analytical sensitivity was estimated in serial dilutions of DNA samples from Sylvio X10 (Tc I) and CL Brener (Tc VI) stocks, as well as from EDTA-treated or heparinized blood samples spiked with known amounts of cultured epimastigotes (CL Brener). LAMP sensitivity was compared after DNA extraction using commercial fiberglass columns or after "Boil & Spin" rapid preparation. Moreover, the same DNA and EDTA-blood spiked samples were subjected to standardized qPCR based on the satellite DNA sequence for comparative purposes. A panel of peripheral blood specimens belonging to Chagas disease patients, including acute, congenital, chronic and reactivated cases (N = 23), as well as seronegative controls (N = 10) were evaluated by LAMP in comparison to qPCR. LAMP was able to amplify DNAs from T. cruzi stocks representative of the six DTUs, whereas it did not amplify DNAs from Leishmania sp, T. brucei sp, T. rangeli KPN+ and KPN-, P. falciparum and non-infected human DNA. Analytical sensitivity was 1x10-2 fg/μL of both CL Brener and Sylvio X10 DNAs, whereas qPCR detected up to 1x 10-1 fg/μL of CL Brener DNA and 1 fg/μl of Sylvio X10 DNA. LAMP detected 1x10-2 parasite equivalents/mL in spiked EDTA blood and 1x10-1 par.eq/mL in spiked heparinized blood using fiberglass columns for DNA extraction, whereas qPCR detected 1x10-2 par.eq./mL in EDTA blood. Boil & Spin extraction allowed detection of 1x10-2 par.eq /mL in spiked EDTA blood and 1 par.eq/ml in heparinized blood. LAMP was able to detect T.cruzi infection in peripheral blood samples collected from well-characterised seropositive patients, including acute, congenital, chronic and reactivated Chagas disease. To our knowledge, this is the first report of a prototype LAMP kit with appropriate analytical sensitivity for diagnosis of Chagas disease patients, and potentially useful for monitoring treatment response.